Distributed vacuum membrane distillation driven by direct-solar heating at ultra-low temperature. (15th January 2022) - Ma, Qiuming; Xu, Zhenyuan; Wang, Ruzhu; Poredoš, Primož
Abstract: Membrane distillation (MD) process is capable of utilizing ultra-low temperature heat (<50 °C), and its compact configuration permits a small module size. Thus a distributed MD device driven by low-grade solar energy for household desalination becomes viable. In this paper, direct solar-heating schemes for vacuum MD (VMD) by photothermal membrane (VMD-PM) and by solar absorber-plate (VMD-FPC) are comparatively analyzed under identical operating conditions. Such a comparison allows for a better understanding of the performance improvement brought by the new structure (VMD-PM) as well as its mechanism. A comprehensive model considering geographical location, date & time, solar absorption, pore diffusion, and dynamic variation etc. was built for performance evaluation. Results revealed that VMD-PM system could achieve a distillate production of 7.14 L m −2, 4.1% higher than VMD-FPC in a 10-h operation with 22.8 MJ m −2 of solar energy. Considering heat recovery for both systems, an even bigger difference in production, up to 11.7% could be observed. Such performance elevation is attributed to the localized heating at membrane surface and more efficient conversion of solar energy to evaporation heat. Results also indicated that utilizing photothermal membranes can indeed relieve the issue of temperature polarization. However, such phenomenon cannot be entirely eliminated. Highlights: Low-temperature VMD heated by photothermal membrane and by absorber-plate is compared. 4.1% enhancement in production by VMD with photothermal membrane is indicated. Solar concentration and heat recovery massively increase VMD performance. The advantage of photothermal membrane is slightly amplified with heat recovery. Temperature polarization can only be eliminated at low permeate fluxes.